Solving equations in two unknowns requires two independent equations. Since you have only one equation there is no solution.
Chat with our AI personalities
2x + 3y = 29x= 4 find x 29x= 4 x = (4/29) sub x into the first part of the sum 2x + 3y = 4 2*(4/29) + 3y = 4 note * means multiply (8/29) + 3y = 4 3y = 4 - (8/29) 3y = (108/29) note 4* 29 minus 8 = 108 y = (36/29) there is probably a quicker way to do this.
2x + 5 = 13 2x = 8 2x/2 = 8/2 x=4
x + 3y = 62x + y = -8Solve by substitution:x + 3y = 6 subtract 3y to both sidesx = 6 - 3y2x + y = -8 substitute 6 - 3y for x2(6 - 3y) + y = -812 - 6y + y = -812 - 5y = -8 subtract 12 to both sides-5y = -20 divide by -5 to both sidesy = 4x = 6 - 3yx = 6 - 3(4) = 6 - 12x = -6Thus, the solution of the system is (-6, 4).
Since 7x + 13x +2x + 8 is an expression (there is no equal sign), there is no answer as to what x equals. However, this expression can be simplified to 22x + 8.
y=6x-16 y=-2x+8